Politics and the media : intersections and new directions / Jane Hall. - Hall, Jane (Professor of journalism) (CQ Press, 2022)
'Politics and the Media' examines how media and political institutions interact to shape public thinking and debates around social problems, cultural norms, and policies. From the roles of race and gender in American politics to the 2020 elections and global coronavirus pandemic, this is an extraordinary moment for politicians, the news media, and democracy itself. Hall explores how media technologies, practices, and formats shape political decision making; how political forces influence media institutions; and how public opinion and media audiences are formed.